(untitled) (International Journal of Occupational Safety and Health, 2025)
Introduction: Healthcare workers (HCWs) face a significant risk of contracting tuberculosis (TB), especially in regions with a high incidence of the disease. In India, routine screening and surveillance data are scarce for TB among HCWs. Our objective was to conduct TB screening among nurse clinicians to address guidelines and policies in the health sector. Methods: An analytical observational study was done in a tertiary care teaching hospital in western Rajasthan, India. Four hundred twenty-two nurse clinicians were recruited and screened for tuberculosis. The tuberculin skin test was conducted according to the latest recommendations and standards to obtain the results. Informed consent was obtained before the procedure was performed. Results: 12.3% showed positive tuberculin test results, while 87.7% tested negative. Past positive history of tuberculosis and current signs and symptoms of tuberculosis are inversely correlated with the likelihood of having tuberculosis. In contrast, past contact with a tuberculosis patient is slightly positively associated with an increased risk of tuberculosis. Conclusion: This study supports the prioritization of clinical nurses as a high-risk group for TB infection, underscoring the importance of considering demographic factors in TB screening and prevention efforts.